INDONESIA EDUCATION PORTRAITS WHEN PANDEMIC COVID-19 - Maslahah Maslahah (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2022)
Different but still one, Indonesia is used to various situations but the situation that occurs is very different from the habit. Not only Indonesia, but foreign countries are also feeling the impact of the Covid-19 virus. Various sectors in the government were affected, including the education sector. Education is experiencing tremendous shocks in this situation, the implementation of teaching and learning activities, but must not stop. Various efforts have been made by the government to keep it optimal even though the situation cannot be optimized. This research illustrates how the portrait of Indonesian education during the Covid-19 pandemic. Besides, this research also presents the nature of education, indigenous education, and a little preview of the new normal period. In this study, the authors used a qualitative research approach to field studies with observation techniques and documentation. In addition, the study used various references sourced from 11 reputable national journal articles, the Covid-19 cluster website, 2 bare books, and documents from the Ministry of Education and Culture.The result of the research states that education is trying to understand everything that is in the universe, all-natural phenomena that occur not by chance, because of the will of the creator. The new normal period is a transitional period with new habits, the author calls it a transitional period because in life everything that is done is still within a limit. The portrait of Indonesian education during the pandemic continues to adapt to the situation, various color zones are set to indicate whether education can be carried out face-to-face or through networks. Various efforts are continuously being made to create the ideal education that is currently happening.